Assessment of heavy metal contamination in surface sediments: Seasonal influence in the Majes-Camaná basin of the Arequipa region, Peru - María Claudia Cáceres Obada; María Eduarda Fernanda Zegarra Oliveira; Naysha Yamelit Meza Elguera; Stephanie Elena Sosa Pulcha; Abdel Alejandro Portocarrero Banda; Jhon Alfredo Quispe Ortiz; Verónica Salinas Murillo; Hugo Guillermo Jiménez Pacheco (Results in Engineering)
The conducted research aimed to identify the presence of environmental contamination by heavy metals in sediments in the Majes - Camaná basin in the Arequipa-Peru, using indicators such as the Geo-accumulation Index (Igeo) and the Pollution Load Index (PLI). A comparison was made with the values proposed by the Interim Freshwater Sediment Quality Guidelines (ISQGs) and Probable Effect Levels (PELs) from the Canadian Sediment Quality Guidelines for the Protection of Aquatic Life, allowing a quantitative evaluation of the environmental impact of 07 heavy metals (Zn, Cu, Cr, Ni, As, Pb, and Cd) along the study points, and to distinguish the possible sources of contamination using box and whisker concentration profiles, mining registries, and vegetation cover by anthropogenic activities. The results from the 07 sampling points indicated significant variation in physicochemical properties, including pH values, conductivity, salinity percentage, Total Dissolved Solids (TDS), and Dissolved Oxygen (DO) between flood and low-water seasons. For ISQGs values, arsenic exceeded the concentration at all points, PM-01, PM-05, and PM-07 exceeded in cadmium, and PM-06 only in copper. There was a predominance of Zinc due to anthropogenic activities in both seasons. Additionally, the general behavior for both periods follow the order: Zn > Cu > Cr > Ni > As > Pb > Cd. Finally, there was no metal contamination with a PLI of 1.012 and 0.778 for low-water and flood seasons, respectively. For copper and chromium metals, light to moderate contamination was found according to Igeo in the low-water season, while low metal concentrations were reported during the flood season. Additionally, biological indicators were evaluated, highlighting the presence of the Chironomidae family, which reflected the water quality in the Camaná River. This bioindicator scored 2 on the BMWP index, categorizing the water as of low quality, which evidences a significant influence of anthropogenic activities in the area.